Which tests can most effectively indicate the clinical phenotype of paediatric haemophilia patients with prophylaxis?. Issue 4 (June 2021) - Ay, Yilmaz; Toret, Ersin; Gozmen, Salih; Cubukcu, Duygu; Karapinar, Tugba Hilkay; Oymak, Yesim; Vergin, Raziye Canan
Abstract : N/A: Patients with haemophilia A who have similar FVIII levels show clinical heterogeneity, and 10–15% of patients with severe haemophilia do not have a severe bleeding phenotype. The aim of this study was to assess whether global haemostasis tests, such as thrombin generation assay (TGA) and thromboelastography (TEG), can predict the bleeding pattern of severe haemophilia better than trough levels and pharmacokinetic profiles, particularly in the prophylactic setting. The study group consisted of 39 patients with haemophilia A and 75 healthy controls. The annual bleeding rate (ABR) and Hemophilia Joint Health Score 2.1 (HJHS) of the patients were determined. Basal factor FVIII, inhibitor levels, TEG and TGA of participants with prophylaxis were performed after a washout period. Then, a recombinant FVIII product was administered to patients. After factor replacement, the above tests were repeated at 30 min, 6 and 48 h. There was a significant difference in the ABR and HJHS between the groups according to the basal factor VIII activity of patients after wash-out. TEG and TGA parameters of patients with factor activity above 1% were significantly better than those of patients with factor activity below 1%. After factor concentrate administration, factor activities, TEG and TGA parameters at 30 min, 6 and 48 h were similar in the two groups. We showed that the 1% trough level but not for the 3% trough level is critical for both clinical phenotypes and thrombin generation for haemophilia patients in the prophylactic setting.